2020
DOI: 10.1371/journal.pone.0232721
|View full text |Cite
|
Sign up to set email alerts
|

S100B single nucleotide polymorphisms exhibit sex-specific associations with chronic pain in sickle cell disease in a largely African-American cohort

Abstract: Background Pain in sickle cell disease (SCD) is severe and multifaceted resulting in significant differences in its frequency and intensity among individuals. In this study, we examined the influence of S100B gene single nucleotide polymorphisms (SNP) on acute and chronic pain variability in SCD. Methods Composite pain index (CPI) scores captured chronic pain. Painful crisis related emergency care utilization recorded acute pain incidence. Genotyping was performed using MassAR-RAY iPLEX platform. Results Regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 59 publications
0
10
0
1
Order By: Relevance
“…We identified 571 manuscripts published before May 16, 2023, reporting genotype-phenotype associations across 29 670 unique individuals (50% ≤ 18 years of age) from 43 countries (eMethods, eFigures 1 and 2, and eTable 5 in Supplement 1 ; eTable 1 in Supplement 2 ). 8 , 11 , 12 , 13 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 571 manuscripts published before May 16, 2023, reporting genotype-phenotype associations across 29 670 unique individuals (50% ≤ 18 years of age) from 43 countries (eMethods, eFigures 1 and 2, and eTable 5 in Supplement 1 ; eTable 1 in Supplement 2 ). 8 , 11 , 12 , 13 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ,…”
Section: Resultsmentioning
confidence: 99%
“…A total of 571 publications passed this screening (eFigure 1 in Supplement 1 , eTable 1 in Supplement 2 ). 8 , 11 , 12 , 13 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ...…”
Section: Methodsunclassified
“…Dyal et al39 found that women were more likely to have sensitization; however, most quantitative sensory testing studies in SCD40–43 and questionnaire-based studies35,38,44 have found no association between sex and NP. S100B gene single nucleotide polymorphisms have been found to be linked to CP, of which NP is a component, in the females of an SCD cohort, but not the males 45. More studies are needed to determine possible genetic and hormonal explanations for this sex difference in SCD.…”
Section: Discussionmentioning
confidence: 98%
“…S100B gene single nucleotide polymorphisms have been found to be linked to CP, of which NP is a component, in the females of an SCD cohort, but not the males. 45 More studies are needed to determine possible genetic and hormonal explanations for this sex difference in SCD.…”
Section: Discussionmentioning
confidence: 99%
“…[470], Jang et al [471], de Frutos et al [472], Lin et al [473], Wang et al [474] [512], von Vietinghoff and Kurts [513], Menendez-Castro et al [514], Kurata et al [515], Yeo et al [114], Lee et al [516], Huang et al [117], Lee et al [517], Stroo et al [518], Lee et al [519], Feng [520], Qin et al [521], Oliveira et al [522], Yang et al [523], Yahya et al [130], Allegretti et al [524], Díez et al [303] and Park et al [525] found that ALB (albumin), ERRFI1, MTNR1A, EGR1, DUSP1, GATA6, TET2, MAGI2, AFP (alpha fetoprotein), KLF15, GATM (glycine amidinotransferase), EGF (epidermal growth factor), LPL (lipoprotein lipase), PPARGC1A, PKHD1, NPHP3, PLG (plasminogen), NR4A1, AVIL (advillin), STRA6, CUBN (cubilin), OGT (O-linked N-acetylglucosamine (GlcNAc) transferase), RGS2, ILK (integrin linked kinase), RBFOX1, DDIT4, RYK (receptor like tyrosine kinase), ERBB4, PTGER3, KCNK5, SPRY2, TRPC1, KL (klotho), GCLC (glutamate-cysteine ligase catalytic subunit), LRP2, NOX4, RGS1, S100A12, PLEKHH2, SORCS1, ATP6V1C2, FKBP5, CA3, IRF9, ELL2, PFKFB2, ATP6, CCL22, SAA1, CCL24, CD5L, CHGA (chromogranin A), CNR2, DBH (dopamine beta-hydroxylase), TNFSF11, XCL1, ELANE (elastase, neutrophil expressed), IFNG (interferon gamma), MPO (myeloperoxidase), CD70, IRF4, VAV1, LYZ (lysozyme), BTK (Bruton tyrosine kinase), LCN2, EPHB2, TREM2, PLD4, JAK3, KCNN4, CCR5, CX3CR1, IL11, TRPM2, TNF (tumor necrosis factor), SEMA7A, TLR7, CCL8, NOD2, CCR2, CCL5, WNT7A, SIGLEC1, DOK3, NOS3, SIGLEC7, RETN (resistin) and S100B are closely related to the development of other kidney diseases. [540] and Cai et al [541] that ALB (albumin), LPL (lipoprotein lipase), KL (klotho), UGT2B7, IFNG (interferon gamma), MPO (myeloperoxidase), BTK (Bruton tyrosine kinase), CD209, KCNN4, CCR5, TNF (tumor necrosis factor), CCR2, CCL5, NOS3, S100B and HBB (hemoglobin subunit beta) are associated with progression of sickle cell disease. Studies showed that altered expression of MTNR1A [542], GATA6 [543], EGF (epidermal growth factor) [544], LPL (lipoprotein lipase) [545], PPARGC1A…”
Section: Discussionmentioning
confidence: 99%